Seasonal variation of gelatinous plankton consumption by fish in the South-western Atlantic Ocean: a question of strategy*. Issue 7 (9th August 2018) - Diaz Briz, Luciana; Sánchez, Felisa; Marí, Noemí; Genzano, Gabriel
ABSTRACT: Gelatinous plankton is an important food resource for several species of fishes in the Southwestern Atlantic Ocean. Some fish depend heavily on these organisms and are specialized to feed on ctenophores, salps and medusae, while others only consume gelatinous plankton occasionally. We hypothesize that consumption of gelatinous plankton by fishes represents an alternative food resource when primary prey are not available during cold periods in the study area. To determine seasonal variations of gelatinous plankton consumption by fishes, data samples were grouped into cold and warm periods. A total of 64, 567 stomachs belonging to 106 species of fish were analysed, of which 32, 943 (51%) contained food items. Of those containing food items, 2719 (8.2%), from 38 fish species, contained gelatinous items. Fourteen species ingested gelatinous in warm period, nine in cold period, and 15 in both periods. The proportion of stomachs with gelatinous was significantly greater during the cold period. Ctenophores were the most predominant prey in both periods, followed by salps and medusae. Consumption of ctenophores, salps and medusae was unevenly distributed within the area during the different periods. Classification methods (group average sorting utilizing Bray–Curtis similarity measures based on log ( X + 1) identified eight areas of consumption. SIMPER (similarity percentages) analyses revealed that nine fish species contributed most to gelatinous plankton consumption. The seasonal and spatial variation of gelatinous consumption by fish would be related to the availability of food in each period. Strategies of gelatinous consumption, including survival, feeding opportunities and prey specialization, are discussed.